A new black pantheon: Kwezi as an epic of African postmodernity. Issue 2 (4th May 2018) - Wright, Timothy
ABSTRACT: A recent special issue of Journal of African Cultural Studies focusing on the African superhero attests to a continent-wide desire for new imaginings of African identity. As Duncan Omanga notes in that collection, these superheroes are not merely appropriations of American pop culture, but rather syncretic adaptations of the genre for local cultures. This paper examines the South African superhero comic strip Kwezi in this context. Kwezi, I argue, stages a series of entanglements between different forms of black identity in a 'post-transitional' South Africa in which the metanarrative of black emancipation has receded from primacy. I show how the series' array of black superheroes and supervillains functions as a contemporary pantheon of competing versions of black identities – predatory, transformative, traditional – that range from the hypermodern to the 'ethnic'. I then place the strip within the traditions of black modernity that arise from pan-Africanism, arguing that by reference to a deep past that peripheralizes white presence on the continent, the series attempts to construct black identity affirmatively and self-referentially. At the same time, its dispensing with a progressive narrative of modernity centred on the nation-state leads me to characterize this as a 'postmodern' rather than 'modern' narrative of blackness.